Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Moderating Studi Pada UPTD Puskesmas Karangrejo Metro Utara - Fitriani; Suryadi; Mira Agustina (Jurnal Manajemen DIVERSIFIKASI, 2024)
This study was aimed at undertanding the effect of competence and work environment onemployee performance with job satisfaction as a moderating variable at UPTD Public HealthCenter (Puskesmas) at Karangrejo Metro Utara. The role of human resources in theorganization is an important factor in organizational effectiveness and success in achievinggoals. The success and performance of a person at work is highly dependent on work skill,work environment and job satisfaction. Employee welfare is positively related toperformance. Minimum work results are caused by a lack of skills relate to the work so thatthe results are less than optimal. This was a quantitative research, the sample of thisresearch was 35 employees. Data collection techniques used a questionnaire. Meanwhile,data analysis used the Validity Test, Reliability Test, Normality Test, Linearity Test,Homogeneity Test, Multiple Regression Analysis. Interaction Test (MRA), Determination RTest, T Test, and Statistical Hypotesis Test. Where the results were obtained: 1. Competencehas a positive effect on employee performance, if competence is increased then performancewill increase. 2. The work environment has a positive effect on employee performance, so if the work environment increases, performance will increase. 3. Job satisfaction is able toincrease (Strengthen) competency on employee performance at the UPTD Karangrejo HealthCenter 4. Job satisfaction is able to increase (Strengthen) the work environment on employeeperformance at the UPTD Karangrejo Health Center